From a Global Burden to an Engine of Growth: Reframing Climate Policy After Copenhagen - Brookes, Tom (Tufts Archival Research Center, 2005)
Volume 34, Issue 2. Summer After a prolonged build-up, the international climate summit in Copenhagen disappointed many in failing to conclude a legally binding, international treaty. Tom Brookes, managing director of the Energy Strategy Centre, explores the reasons why the conference fell short of expectations and where global climate policy may go from here.